CLINICAL STUDIES REGARDING DENTAL BRUSHING PERFORMANCE: MANUAL VS. THREE-DIMENSIONALLY ELECTRIC BRUSHING: A PROSPECTIVE SPLIT MOUTH DESIGN STUDY - Adrian Tohati; Camelia Tohati; Alexandru Vlasa; Farah Bechir (Romanian Society of Oral Rehabilitation, 2022)
The aim of the present clinical study was to study the efficiency of electric toothbrushing when comparing it to the classical manual Bass method. During our research we looked at the concept of efficiency, the ergonomics of the electric and classic toothbrush, as well as their ability to remove as much as possible the bacterial plaque on the surface of the teeth, from the interdental spaces and from the superficial marginal periodontium. The group consisted of 114 subjects aged between 16-50 years of which 60 were women representing 52.63% and 54 were men representing 47.36%, coming from different social backgrounds. Plaque index (PI) and papilla bleeding indices (PBI) were evaluated during a period of six weeks using the direct method with the dental probe or the indirect method using plaque detectors. At the end of the clinical trial, there were clear differences between the efficiency of electric and manual brushing. When examining the right side brushed manually IP registered values lower than 1 in a number of 64 (56.1%) of the examined persons, the rest of 50 (43 .9%) showing values between 1-1.5. The PBI index on the right-side recorded scores below 0.3 to 43 (37.7%) of subjects, while the remaining 71 (62.3%) had values between 0.3-0.6. On the left-side, sanitized with the electrically operated brush, the average IP with values less than 1 was determined in a number of 103 (90.4%) subjects, the remaining 9 subjects (9 .6%) showing values between 1-1.5. Regarding the values of PBI on the left-side, 91 subjects had values below 0.3 and the remaining 23 (20.2%) patients recorded values between 0.3 -0.6 One explanation for these results is that the easy technique of the electric sanitizing variant leads to a maintenance of the technique unaltered over time, which in the case of manual brushing cannot be verified.